The barbell meets the byte (Ausport, 2003)
Enter Kinetic Performance Technology (KPT), a Canberra-based research and development company specialising in sports performance technology. Researchers and software engineers have designed and developed GymAware, a state-of-the-art system for evaluating and improving athletic performance in the gym. `The GymAware system is a technological bridge linking coaches, athletes and scientists so they can work as a team,` said Rob Shugg from KPT. `We have seen how hard the athletes work, and want to ensure they get the best value out of that work by providing accurate performance feedback. `We are very keen for the AIS to use the system first as we have enjoyed a very good working relationship with the coaches, athletes and scientists and want everyone to benefit from our expertise. We know that the AIS has a great track record in applying cutting-edge technology.`